Implementasi Pendidikan Karakter Berbasis Kearifan Lokal Melalui Transformsi Cerita Rakyat Maluku menjadi Video Animasi dalam Pembelajaran Bahasa Indonesia - Aria Bayu Setiaji (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2022)
Abstract This study aims to describe the implementation of character education through the use of animated videos of Maluku folktales in Indonesian language learning. The study used a descriptive qualitative approach, with data sources consisting of teachers and students involved in animated video-based learning of Maluku folktales. Data were collected through observation, interviews, and documentation, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results indicate that animated videos of Maluku folktales effectively internalize character education values, such as brotherhood, tolerance, mutual cooperation, responsibility, social awareness, and independence. The use of audiovisual media also increases student interest, attention, and participation in learning. In addition to functioning as a learning medium, animated videos of folktales contribute to the preservation of local wisdom and the strengthening of the Pancasila Student Profile. These findings demonstrate that the integration of local wisdom and digital media can be an innovative, contextual, and relevant learning strategy to meet the demands of 21st-century education. Keywords: character education, Maluku folktales, animated videos, Indonesian language learning, local wisdom